Choosing Laboratory Tests in an Evidence-based manner; a Letter to Editor - Hashemi, Reza (Archives of Men’s Health, 2023)
Physicians use a variety of para-clinical tests to confirm their diagnosis. There are some common ways to use these tests: 1- Parallel strategy means to request all the necessary tests in one step, and 2- Serial strategy, which is of two types: “serial or” and “serial and”. (1) In the former type, the doctor first requests test A and if it is negative, requests test B. But in the latter type (serial and), despite the positiveness of test A, they also ask for test B to eliminate possible doubts.